DIGITAL TRANSFORMATION AS A STRATEGIC INNOVATION IN ISLAMIC EDUCATION GOVERNANCE IN THE ERA OF SOCIETY 5.0 - Andini Naziela El-Khusna; Subaidi Subaidi; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the role of digital transformation as a strategic innovation in Islamic education governance in the era of Society 5.0. The research employs a library research method by reviewing books, scientific articles, and national and international journals related to digital transformation and Islamic education governance. Data were analyzed using content analysis through the stages of identification, classification, interpretation, and synthesis of relevant literature. The findings indicate that digital transformation plays a strategic role in Islamic education governance by shifting from a mere administrative support system to a key driver of governance reform that enhances effectiveness, efficiency, transparency, and accountability. It also supports data-driven decision-making, improves the quality of educational services, and expands access to educational information through integrated digital systems. Furthermore, digital transformation should be understood as a holistic process that integrates technological advancement with Islamic values and human-centered principles in line with the Society 5.0 paradigm. However, its implementation faces challenges such as limited technological infrastructure, low digital literacy, resistance to organizational change, and insufficient integration of Islamic ethical values in digital governance systems. Therefore, strengthening institutional policies, digital competencies, leadership capacity, and value-based governance frameworks is essential to ensure sustainable transformation in Islamic education. The study concludes that digital transformation is not only a technological innovation but also a paradigm shift in Islamic education governance toward a more adaptive, ethical, and human-centered system.